Fauna parasitária de peixes oriundos de pesque-pague do município de Guariba, São Paulo, Brasil - Schalch, Sergio Henrique Canello [UNESP]; De Moraes, Julieta Rodini Engracia [UNESP]; De Moraes, Flávio Ruas [UNESP] (Universidade Estadual de Maringa, 2006)
This study describes the occurrence and the seasonality of parasites of cultivated fish from a fee fishing farm located in Guariba, São Paulo State, Brazil (21°15'22'' S, 48°18'58'' W and 595 m of altitude), from August, 2001 to July, 2002. The presence of parasites was researched in pacu Piaractus mesopotamicus (Characidae), common carp Cyprinus carpio (Cyprinidae), nile-tilapia Oreochromis niloticus (Cichlidae), tambacu hybrid (male of P. mesopotamicus x female of tambaqui-Colossoma macropomum) and piraputanga Brycon hillari (Characidae). Results demonstrate that out of 100 fish examined, 15% were sponged for at least one of the following parasites: Trichodina sp.; monogenean helminths; copepodits of Lemaea cyprinacea; adults of L. cyprinacea; or Dolops carvalhoi. In decreasing order, the susceptibility degree of the hosts was C. carpio, P. mesopotamicus, B. hillari, tambacu hybrid and O. niloticus. In decreasing order the reported parasites were monogenean helminths, Dolops carvalhoi, Trichodina sp., adults of Lernaea cyprinacea and their young shapes.
Parasitic fauna of cultivated fishes in fee fishing farm of Guariba, São Paulo State, Brazil
Keywords: Fee fishing farm; Fish; Parasites; Seasonality; Brazil; Brycon hillari; carp; cichlid; controlled study; Cypriniformes; Dolops carvalhoi; fauna; fish; fishery; helminth; host parasite interaction; Lernaea cyprinacea; nonhuman; parasite; Piaractus mesopotamicus; seasonal variation; Trichodina; Brycon; Characidae; Cichlidae; Colossoma macropomum; Colossoma marcopomum; Cyprinidae; Cyprinus carpio; Monogenea; Oreochromis niloticus; Pisces; Vermes